John Cage. A mycological foray - Cage, John 1912-1992; Trinder, Kingston; Pellerin, Ananda (Atelier Éditions, 2020)
John Cage: A Mycological Foray' draws readers across the idiosyncratic, mushroom-suffused, innermost landscape of celebrated American composer John Cage. Upon the remarkable journey with Cage, one encounters assorted photographs, compositions, and contemplations; all in the very same unexpected fashion one encounters various flora and fungi species while mushroom foraging. Volume I encompasses Cage?s mycological-oriented Indeterminacy stories, Diary excerpts, and essays; and the complete transcript of Cage?s 1983 performance, 'MUSHROOMS et Variationes'. Volume II offers the inaugural reproduction of Cage?s 1972 portfolio, 'Mushroom Book'; authored in collaboration with illustrator Lois Long and botanist Alexander H. Smith. 00